Hypernatremia in brain‐dead patients. Issue 5 (22nd April 2022) - Guo, Weixin; Wang, Shouhong; Wang, Zhonghua; Hu, Peihang; Wei, Xuebiao; Liao, Xiaolong
Abstract: Objectives: Hypernatremia often occurs in patients with brain death. This study summarizes its characteristics. Methods: We recorded 57 patient's highest blood sodium value, as well as daily NT‐proBNP, blood creatinine, and urine output. Further, we analyzed the time of the first rise in blood sodium, and the relationship between NT‐proBNP, serum creatinine, urine output, and serum sodium. Results: There was no hyponatremia in these patients, and only seven of the 53 patients registered blood sodium between 137 and 150 mmol/L. We found that blood sodium started to rise at 36.0 (28.5–52.3) h, reaching the highest value in 79.0 (54.0–126.0) h. Urine volume and creatinine have no correlation with serum sodium level, while NT‐proBNP has a significant correlation with serum sodium level. Conclusion: It is necessary to conduct volume assessments and urine electrolyte testing on patients with brain death. BNP has a protective effect on water and electrolytes to prevent hypernatremia. Abstract : It is necessary to conduct volume assessments and urine electrolyte testing on patients with brain death. BNP has a protective effect on water and electrolytes to prevent hypernatremia.